The undoing of Saint Silvanus [large type] - Moore, Beth, 1957- (Thorndike Press, 2016)
Jillian Slater hadn't seen her father or his mother in almost 20 years until, on the news that her father had finally drunk himself to death, Adella Atwater, the manager of her grandmother's apartment house, calls and says Jillian's expenses would be paid if she'd fly in to New Orleans for the burial. What Adella didn't tell her was that the apartment house bears the dead weight of a long and painful history. As an investigation into her father's death unfolds, Jillian is drawn into the lives of the colorful collection of saints and sinners who pass through Saint Silvanus. Is her family actually cursed, or is it just this crazy old house that holds them all under its spell?